The Changing Learning Technological Landscape for Trainers in the Wake of COVID-19. Issue 1 (February 2021) - Hughes, Claretha
The Problem: Due to the unexpected and rapid spread of COVID-19 throughout the world, training professionals are faced with three distinct problems: (1) lack of technological infrastructure; (2) the conflict between essential and non-essential workers; and (3) the ability to rapidly train workers to use new technology while working from home. Trainers are seeking to help workers and organizations use learning technologies to navigate the continuously changing workplace landscape in the midst of and after the COVID-19 pandemic. The Recommendation: Forced expansion of learning technologies by trainers during COVID-19 provides an opportunity to expand worker development. Not only will trainers expand their knowledge of the use of technology, they will also become better proficient at selecting appropriate technology for employee development. Trainers should become better advocates for the use of technology by demonstrating their own expertise in using learning technologies; use their communication skills to teach workers about context and how to transition current skills into new jobs; and help workplace leaders better understand how technology and people can co-exist in the workplace. Stakeholders: The stakeholders who can benefit from this article are trainers, workplace leaders, workers who are forced to work from home, essential workers who must go to work each day, displaced workers, furloughed workers, and laid off workers.